Bacillus cabrialesii subsp. cabrialesii Strain TE5: A Promising Biological Control Bacterium Against the Causal Agent of Spot Blotch in Wheat - Ixchel Campos-Avelar; Michelle Fabiela García Jaime; Pamela Helué Morales Sandoval; Fannie Isela Parra-Cota; Sergio de los Santos Villalobos (Plants)
Strain TE5 was isolated from a wheat (Triticum turgidum L. subsp. durum) rhizosphere grown in a commercial field of wheat in the Yaqui Valley in Mexico. In this work, we present strain TE5 as a promising biological control agent against Bipolaris sorokiniana. First, after its genome sequencing through Illumina NovaSeq, this strain showed a genome size of 4,262,927 bp, with a 43.74% G + C content, an N50 value of 397,059 bp, an L50 value of 4 bp, and 41 contigs (>500 bp). Taxonomical affiliation was carried out by using overall genome relatedness indexes (OGRIs) and the construction of a phylogenomic tree based on the whole genome. The results indicated that strain TE5 identifies with Bacillus cabrialesii subsp. cabrialesii. Genomic annotation using Rapid Annotation Using Subsystems Technology (RAST) and Rapid Prokaryotic Genome Annotation (Prokka) indicated the presence of 4615 coding DNA sequences (CDSs) distributed across 330 subsystems, which included gene families associated with biocontrol, stress response, and iron competition. Furthermore, when the antiSMASH 7.1 platform was used for genome mining, the results indicated the presence of seven putative biosynthetic gene clusters related to the production of biocontrol metabolites, namely subtilosin A, bacillibactin, fengycin, bacillaene, bacilysin, surfactin, and rhizocticin A. Moreover, the antifungal activity of strain TE5 and its cell-free extract (CFE) was evaluated against Bipolaris sorokiniana, an emergent wheat pathogen. The results of in vitro dual confrontation showed fungal growth inhibition of 67% by strain TE5. Additionally, its CFE almost completely inhibited (93%) the growth of the studied phytopathogenic fungus on liquid media. Further observations of the impact of these bacterial metabolites on fungal spore germination exhibited inhibition of fungal spores through degrading the germinative hypha, avoiding mycelium development. Finally, the protective effect of strain TE5 against Bipolaris sorokiniana was evaluated for wheat seedlings. The results showed a significant decrease (83%) in disease severity in comparison with the plant infection without inoculation of the biological control agent. Thus, this work proposes Bacillus cabrialesii subsp. cabrialesii strain TE5 as a promising biological control agent against the wheat pathogen Bipolaris sorokiniana while suggesting lipopeptides as the potential mode of action, together with plant growth and defense stimulation.